2022
DOI: 10.1021/acs.iecr.2c02092
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Activity of Iron Nanoparticles in Both Thermal and Plasma Driven Catalytic Ammonia Decomposition

Abstract: Water-dispersible Fe 3 O 4 nanoparticles with diameters of 4.2 ± 0.6, 6.1 ± 0.8, 8.1 ± 1, and 10.4 ± 1 nm were prepared through the polyol method and employed as the precursors of Fe 3 O 4 /Al 2 O 3 catalysts to study the size-dependent activity. We identified that the activity of the catalysts in NH 3 decomposition (driven by both thermal and dielectric barrier discharge plasma) increased with increasing Fe 3 O 4 particle size. The turnover frequencies (TOFs) were increased from 0.9 to 5.8 s −1 with an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 45 publications
(89 reference statements)
0
20
2
Order By: Relevance
“…The reactor system has been shown in our previous report, although the specific reactor parameters are different. 48 Specifically, a 6 cm long stainless steel mesh (20 mesh) was employed as the outer electrode and wrapped tight around the quartz tube. The out electrode was wrapped with ceramic fiber for insulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactor system has been shown in our previous report, although the specific reactor parameters are different. 48 Specifically, a 6 cm long stainless steel mesh (20 mesh) was employed as the outer electrode and wrapped tight around the quartz tube. The out electrode was wrapped with ceramic fiber for insulation.…”
Section: Methodsmentioning
confidence: 99%
“…The DBD plasma-assisted carbonization was performed in a coaxial DBD reactor consisting of a quartz tube with an inner diameter of 7 mm and an outer diameter of 3/8″. The reactor system has been shown in our previous report, although the specific reactor parameters are different . Specifically, a 6 cm long stainless steel mesh (20 mesh) was employed as the outer electrode and wrapped tight around the quartz tube.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, particle size dependence on ammonia conversion and energy efficiency over unmodified alumina support material has also been reported by El-Shafie et al 185 Although more description about the nature of alumina used was not reported in this study, the authors observed that increasing the alumina particle size from 1 to 2 mm led to a decrease in NH 3 conversion from 83.19% to 80.35%, with a corresponding decrease in energy efficiency. 185 Chen et al 186 studied the particle size dependence of Fe on the NH 3 conversion with a particle size range of 4.2−10.4 nm. Different Fe 2 O 3 nanoparticles were prepared using the polyol method and dispersed on the Al 2 O 3 using impregnation techniques.…”
Section: Advancements and Currentmentioning
confidence: 99%
“…DBD reactor together with Fe 3 O 4 catalysts was also studied by Chen et al in 2022, who showed that the activity increased with increasing particle size. 102 2.3. Electrolysis for Ammonia Cracking.…”
Section: Catalysts Combining Plasmamentioning
confidence: 99%
“…They concluded that the SiO 2 material can be utilized as a catalyst, in view of enabling lower costs compared to Ru materials. DBD reactor together with Fe 3 O 4 catalysts was also studied by Chen et al in 2022, who showed that the activity increased with increasing particle size …”
Section: Ammonia Decomposition Technologiesmentioning
confidence: 99%